(untitled) (Международный научный журнал «Инженер», 2026)
Climatic changes affect the melting dynamics of the snow cover and the amount and shape of atmospheric precipitation, causing an increase in the periodicity and duration of floods. There are several types of floods, and floodplains occupy a special place in our republic in the placement of arid in the region. The topographic appearance of the area along with the amount of atmospheric precipitation, natural drainage opportunities and the land use situation in the area play an important role in the origin of floods. 12% of the territory of the Republic of Uzbekistan is considered to be regions of flood risk. The paper used numerical statistical analysis methods for flood analysis and identification of potentially hazardous areas. In the Republic, there is a constant decrease in the amount of total water resources used in the last 10 years. Against the background of the quantitative decrease in water resources, it was found that the recurrence of floods is increasing. Based on the results of the analysis, it was found that Surkhandarya, Kashkadarya and Jizzakh regions of the Republic came in Category II and III on the risk of flooding, the perennial average return of flooding was 3 and higher.